Loan collateral, corporate investment, and business cycle - Aivazian, Varouj; Gu, Xinhua; Qiu, Jiaping; Huang, Bihong (Journal of Banking & Finance, 2015)
Collateral and loan rates are observed to be highly cyclical in their use for bank lending. The effects of such cyclicality on corporate investment are analyzed in this paper using a dynamic model. We find that more collateral causes firms to select riskier (/safer) projects if the loan rate rises above (/falls below) the expected investment return. We show that the incentive effect of loan rates becomes stronger with greater collateral, with the two credit terms having larger incentive effects on lower-quality firms. These results offer a new explanation for why lenient collateral policies are associated with rising loan rates in economic upturns but stricter collateral requirements come with falling loan rates during downturns.